Minat Siswa Madrasah Tsanawiyah Al-Falah Pulubala terhadap Bela Diri Shorinji Kempo - Ahmad Lamusu; Zulkifli Lamusu; Arief Ibnu Haryanto (Journal on Education, 2023)
Currently, Shorinji Kempo martial arts in Gorontalo are well-known among children, youth, adults to the elderly, many of them even take part in Shorinji Kempo training at dojos spread across Gorontalo Province. This study aims to find out how much interest students at MTs Al-Falah Pulubala District have in learning Shorinji Kempo. This research is a descriptive research using survey method. This research was conducted at the Madrasah Tsanawiyah (MTs) Pulubala, Pulubala District, Gorontalo Regency. The population in this study were all students at MTs Pulubala, Pulubala District, Gorontalo Regency, totaling 41 students. The sampling in this study used a purposive sampling technique with the requirements 1) being an active student, 2) being active in sports activities, 3) being willing to be a sample. Based on the purposive sampling technique, a total of 15 samples were obtained. The instrument in this study used a closed questionnaire whose validity had been measured. As a result, students' interest in Shorinji Kempo martial arts showed that the average student interest was 72.67% which indicated that out of 15 students, 10 students were interested in learning Shorinji Kempo martial arts and 2 students were very interested, and 2 students were less interested. Based on the results of the study entitled Survey of Interest in Studying Shorinji Kempo Self Defense for Students of MTs Pulubala, Pulubala District, Gorontalo Regency, it was found that out of 10 students at MTs Al-Falah Pulubala had an interest in shorinji kempo martial arts.